Study on scientific productivity determination and scientific productivity improvement of rock burst mine - Feng CUI; Zhong LUO; Xingping LAI; Jianqiang CHEN; Baoshan PENG; Lei ZOU; Xudong LIU (Meitan kexue jishu)
China's coal resources with a buried depth of more than 1000 m account for more than 50% of the total reserves, which will be the main part of coal resources supply in the future. It is of great significance to carry out the scientific productivity of rock burst mines and scientifically improve the productivity to ensure the safe and efficient mining of deep coal resources in China. Aiming at the problem of productivity determination and productivity improvement of rock burst mine, the range of mine field containing rock burst coal seam is scientifically divided by theoretical analysis and field monitoring, and the disturbance response characteristics of mining face under different mining methods, mining sequences and mining layouts in rock burst mine are analyzed, the determination method of scientific productivity of rock burst mine is established, and the top-level design and practice method of scientific productivity improvement of rock burst mine are put forward. The research results show that it is necessary to identify the impact tendency and determine the impact risk of the rock burst mine, and to realize the scientific planning of the mine field range with rock burst coal seam; The mining method, mining sequence and layout, and the response characteristics of mining parameters to the disturbance of coal face are studied, and the systematic method of scientific design of coal face in rock burst mine is obtained, which creates conditions for the productivity improvement of rock burst mine. This paper puts forward the technical path to determine the productivity of rock burst mine, and based on mining dynamics, constructs a method to determine the advancing speed of coal face in rock burst mine by stages, regions, periods, unloading pressure and historical prevention and control level. The top-level design of productivity improvement in rock burst mine is constructed, and it is clearly pointed out that the key to control productivity is the impact risk brought by productivity improvement, so as to achieve the balance between mining intensity and unloading pressure and reduce the impact risk, thus effectively improving productivity. The integrated technical path from scientific planning of mine field scope and scientific design of coal face to scientific determination and improvement of productivity in rock burst mine is constructed, which provides scientific guidance for scientific determination and improvement of productivity in rock burst mine.